Disability Rights and Health Justice: Addressing Health Inequities for Disabled Populations in Indonesia (Indonesian Health Justice Review, 2024)
Persons with disabilities in Indonesia face significant barriers to accessing healthcare, contributing to broader health inequities in the country. This paper examines the intersection of disability rights and health justice, focusing on the challenges faced by disabled populations in accessing necessary medical care, rehabilitation, and support services. Using both quantitative data and qualitative interviews with healthcare providers, disability advocates, and individuals with disabilities, the study identifies systemic barriers such as physical inaccessibility, discrimination within healthcare settings, and the lack of specialized healthcare services. The research reveals that while Indonesia’s legal framework provides some protections for people with disabilities, these laws are often not adequately enforced, and healthcare providers lack the training to meet the needs of disabled individuals. The paper argues for comprehensive policy reforms that ensure full access to healthcare for persons with disabilities, including improving physical accessibility, training healthcare professionals, and implementing community-based healthcare models. Recommendations also include better enforcement of disability rights laws and creating a more inclusive healthcare system that guarantees health justice for all Indonesians.